Altruisme, Kerendahhatian Intelektual, dan Karisma, Apakah Mereka Berhubungan? Studi pada Konselor SMA Banjarmasin - Haryadi, Rudi; Sanjaya, Sanjaya (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2023)
The aim of this research is to examine the positive and significant relationship between altruism and intellectual humility on charisma in high school guidance and counseling teachers in Banjarmasin City. This research is quantitative research with a correlational design. Altruism, intellectual humility, and charisma of 66 high school counselors in Banjarmasin City were measured using a scale adapted from Self-Report Altruism (SRA), Comprehensive Intellectual Humility Scale (CIHS), and General Charisma Inventory (GCI). These three scales have been tested as valid and at high (CIHS) and very high (SRA and GCI) levels of reliability. The ANOVA test on the Multiple Linear Regression model was used to analyze the data and prove the hypothesis that was built. The research results show that there is a positive and significant correlation between altruism and intellectual humility together on charisma in high school counselors in Banjarmasin City (Sig. = 0.001 < 0.05) with a contribution level of 20.6%. Based on the results and limitations of this research, it is recommended that future researchers test the relationship between altruism, intellectual humility, and charisma on different and more subject characteristics.